Interest Based Interactivity Through Cross Platform in Big Data - Ansari, Iqbal; Ghimire, Sunil; Chaudhary, Subash; Prasad, Anoop N (International Journal of Computer Sciences and Engineering, 2025)
Given the ubiquity of social media, interest-based interactivity as a main element to intensify user experience. Interest-based relevance modeling is taken out from user influence in multiple-platform social network Big Data container. The main goal of this work is to implement a platform for providing recommendation across different social network based on user interest. The streams consisted of tags from social media content through a discovery process and the application is tested on social media content streams to generate a Big Data scenario.